Penerapan Terapi Relaksasi Benson pada Pasien yang Mengalami Kecemasan Pre Operasi Tumor Ovarium - Uun Octaviani; Siti Haniyah; Fahmi Ayatun (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Anxiety can affect physiological functions in patients prior to surgery, including increased heart rate and respiration, changes in blood pressure and temperature, relaxation of smooth muscles in the bladder, cold and clammy skin, and dry mouth, which may reduce the patient’s energy level. Psychologically, anxiety can lead to increased postoperative pain, delayed wound healing, increased physical disability, and decreased quality of life. One effective non-pharmacological intervention to reduce anxiety is Benson relaxation therapy. Objective: This study aimed to determine the effect of benson relaxation therapy on reducing anxiety levels in pre operative. Methods: This study used a case study design involving one preoperative patient with anxiety symptoms in the Teratai Ward of Prof. Dr. Margono Soekarjo Hospital, Purwokerto. Benson relaxation therapy was administered for 3 days, twice daily, with a duration of 15 minutes per session. Anxiety levels were measured using the Zung Self-Rating Anxiety Scale (ZSAS) before and after the intervention. Results: The patient showed a decrease in anxiety score from 55 (moderate anxiety) to 40 (mild anxiety) after receiving Benson relaxation therapy. Subjectively, the patient reported feeling calmer, more accepting, and motivated. Objectively, there was a reduction in heart rate and physical signs of anxiety. Conclusion: Benson relaxation therapy is effective in reducing anxiety levels in preoperative patients. This intervention can be used as a non-pharmacological alternative to support psychological recovery of pre-operative patients.